Charge Transfer Induces Formation of Stimuli‐Responsive, Chiral, Cohesive Vesicles‐on‐a‐String that Eventually Turn into a Hydrogel. Issue 3 (29th January 2015) - Bhattacharjee, Subham; Bhattacharya, Santanu
Abstract A charge transfer (CT) mediated two‐component, multistimuli responsive supergelation involving a L‐histidine‐appended pyrenyl derivative (PyHisOMe) as a donor and an asymmetric bolaamphiphilic naphthalene‐diimide (Asym‐NDI) derivative as an acceptor in a 2:1 mixture of H2O/MeOH was investigated. Asym‐NDI alone self‐assembled into pH‐responsive vesicular nanostructures in water. Excellent selectivity in CT gel formation was achieved in terms of choosing amino acid appended pyrenyl donor scaffolds. Circular dichroism and morphological studies suggested formation of chiral, interconnected vesicular assemblies resembling "pearls‐on‐a‐string" from these CT mixed stacks. XRD studies revealed the formation of monolayer lipid membranes from these CT mixed stacks that eventually led to the formation of individual vesicles. Strong cohesive forces among the interconnected vesicles originate from the protrusion of the oxyethylene chains from the surfaces of the chiral vesicles.